What is the State of the Evangelical Mind on Christian College Campuses? - Fea, John (Christian scholar's review, 2018)
Does Mark Noll’s The Scandal of the Evangelical Mind still have relevance today, more than two decades after its publication in 1994? As a historian who has spent 16 years in a Christian college affiliated with the Council for Christian Colleges & Universities (CCCU) and a longtime member of evangelical congregations (for the past 16 years I have attended a congregation affiliated with the Evangelical Free Church of America), I can safely say that it has more relevance than ever. In this short essay, I want to reflect on why I believe this to be the case.